2004
DOI: 10.1046/j.1529-8817.2004.00096.x
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA Heterogeneity in Tunisian Berbers

Abstract: SummaryBerbers live in groups scattered across North Africa whose origins and genetic relationships with their neighbours are not well established. The first hypervariable segment of the mitochondrial DNA (mtDNA) control region was sequenced in a total of 155 individuals from three Tunisian Berber groups and compared to other North Africans. The mtDNA lineages found belong to a common set of mtDNA haplogroups already described in North Africa. Besides the autochthonous North African U6 haplogroup, a group of L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
71
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(83 citation statements)
references
References 29 publications
11
71
1
Order By: Relevance
“…The presence of Moroccan Berber H individuals may stem from an initial westward migration of the Egyptian Berbers along the North African coast. This hypothesis is consistent with polymorphic H levels in three Tunisian Berber groups (a mean of 21.4 for the Matama, Sened, and Chenini-Douiret Berbers) (Fadhlaoui-Zid et al 2004), which are positioned geographically between Egypt and Morocco.…”
Section: Evidence For Dispersals Through the Levantine Corridorsupporting
confidence: 82%
See 1 more Smart Citation
“…The presence of Moroccan Berber H individuals may stem from an initial westward migration of the Egyptian Berbers along the North African coast. This hypothesis is consistent with polymorphic H levels in three Tunisian Berber groups (a mean of 21.4 for the Matama, Sened, and Chenini-Douiret Berbers) (Fadhlaoui-Zid et al 2004), which are positioned geographically between Egypt and Morocco.…”
Section: Evidence For Dispersals Through the Levantine Corridorsupporting
confidence: 82%
“…There is also uncertainty regarding the route into Egypt, since no J1b lineages are detected in the Jordanians, the Druze of northern Israel (Macaulay et al 1999) or in the Ethiopians ). The very low frequency of J1b among the Matmata Berbers (0.02) and Tunisian Arabs (0.02) (Fadhlaoui-Zid et al 2004) and its apparent absence in various northwest African groups including two populations geographically close to the Strait of Gibraltar (Moroccan Berbers and non-Berber Moroccans in Rando et al 1998) adds complexity to this issue. It is possible that random genetic drift has erased J1b from many populations along its trail(s) (either through the Levant, from Ethiopia to Egypt and/or from North West Africa to Tunisia) after its introduction into Tunisia and Egypt.…”
Section: Evidence For Dispersals Through the Levantine Corridormentioning
confidence: 99%
“…In fact, when linguistically differentiated Berber and Arab populations from Morocco are compared by their L3A frequencies (6% vs 12%; data from Thomas et al 2002; and our unpublished results), significant differences are found between them (P = 0.007), the Berber frequency being similar to that of the Maure. This L3A difference between Berber and Arab speaking groups is extendable to Argelia (7% vs 15%; P < 0.000; data from Côrte-Real et al 1996;Rosa et al 2004 and our unpublished results) and to Tunisia (10% vs 23%; P = 0.028; data from Plaza et al 2003;Fadhlaoui-Zid et al 2004). The latter significance level would be increased if only the most genetically isolated Tunisian Berbers from Chenini-Douiret were compared.…”
Section: Mauritaniasupporting
confidence: 57%
“…It was initially described (but unnamed) in Tunisian Berbers (Fadhlaoui-Zid et al, 2004), and later also detected in the LCB where its root type (16041-16223), along with several derived types having few matches elsewhere, appears to be very frequent (Černý et al, 2007). It was further suggested that the evolution of L3e5 took place in the LCB region and that its most recent common ancestor lived there ∼11.5 ka (Černý et al, 2007).…”
Section: Introductionmentioning
confidence: 99%